2010
DOI: 10.4103/1596-3519.68366
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of prescription drug use in Nigerian army hospitals

Abstract: The pattern of prescription drug use in Nigerian Army hospitals is unsatisfactory. It is characterised by high number of drugs per prescription, high rate of antibiotic usage and unscientific prescription by doctors. There is a need for further education and research on rational drug use among prescribers in Nigerian military health facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 12 publications
5
45
6
Order By: Relevance
“…(17) Prescribing antibiotics without laboratory validation for its indication promotes multi-drug resistance of microbes which in turn result in using highly potent antibiotics for otherwise mild bacterial infections. (1) In this study, drug usage in the form of injection was found to be 26% that was higher than Patel et al (5.3%) (14) , similar to Adebayo et al (24%) (18) and lower than babalola et al (72.7%).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…(17) Prescribing antibiotics without laboratory validation for its indication promotes multi-drug resistance of microbes which in turn result in using highly potent antibiotics for otherwise mild bacterial infections. (1) In this study, drug usage in the form of injection was found to be 26% that was higher than Patel et al (5.3%) (14) , similar to Adebayo et al (24%) (18) and lower than babalola et al (72.7%).…”
Section: Discussionsupporting
confidence: 68%
“…WHO encourages the use of generic analogue of drugs, as they are cheaper than branded substitutes and have similar effect. (18) Our results in this index were better than Babalola et al (69.8%) (1) , Adebayo et al (49.3%) (18) , Mendonca et al (66%) (12) , Sarkar et al (21%) (19) and Salman et al (4%). (7) Amoxicillin followed by metronidazole, penicillin 800.000, penicillin V, coamoxiclave were the most common prescribed antibiotics respectively.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…It has been reported that Azar Hospital, Golestan University of Medical Sciences 69% (220 cases of 318 admitted patients) had received antibiotics in internal, infectious disease, and surgical wards and ICUs [57]. Same study and several other studies conveyed that irrational prescription of medicine including antimicrobials possibly will result in poor health status and enormous financial impact for any community or country [57][58][59][60][61]. Antimicrobials alone took the share 30-50% of all prescribed medicine in quite a lot of countries [58,62].…”
Section: The Islamic Republic Of Iranmentioning
confidence: 99%
“…Same study and several other studies conveyed that irrational prescription of medicine including antimicrobials possibly will result in poor health status and enormous financial impact for any community or country [57][58][59][60][61]. Antimicrobials alone took the share 30-50% of all prescribed medicine in quite a lot of countries [58,62]. Research Center, Shiraz, Iran reported in Editorial in the most prestigious medical journal the Lancet that "antibiotics are an important front-line instrument in the fight against various infectious diseases.…”
Section: The Islamic Republic Of Iranmentioning
confidence: 99%